The Islamic worldview on the preservation and restoration of mental health - Abdul Razak, Abdul Latif (IIUM Press, 2011)
A worldview has direct impacts on one’s feeling and behavior. One’s positive feeling, for example, is normally the products of one’s positive worldview and vice versa. There are many worldviews available in which some are religious, while some are irreligious or secular in nature. Some are comprehensive covering all realms of existence, while some are limited to the material world only. Since feeling and behavior are closely related to worldview, therefore a person’s state of mental health strongly depends on the nature of worldview that he or she embraces. This paper aims at analyzing the significance of Islamic worldview in preserving mental health as well as in restoring its healthy state. For this purpose, the paper begins with the discourse on the weaknesses of the existing modern Western psychotherapies which are founded upon secular and materialistic worldviews. This is followed by an elaboration of the elements of the Islamic worldview that have great significance in preserving mental health and curing its illnesses. The outcome of this is the introduction of a new psychotherapeutic approach which is divinely rooted (al-rabbÉniyyah), characterized by comprehensiveness (al-shumËl), consistency (al-thubËt), certainty (al-yaqÊn), and suitability with the nature of man (fiÏrah) in coping with modern challenges. It is hoped that this paper which is based on the study of the Qur’an, Sunnah and the works of early Muslim psychologists and psychotherapists will enlighten us on the importance of religious worldview especially Islamic worldview on mental health.